Utilization of Date Palm Trunk Fibers (DPTFs) Waste as a Sorbent for the Removal of Crude Oil from Aqueous Media: Equilibrium Isotherms and Kinetic Studies - Hamid Boleydei; Zahra Razavi (Iranian Journal of Health, Safety and Environment, 2018)
In the present study, the efficiency of date palm trunk fibers (DPTFs) to remove crude oil from aqueous solution was evaluated. The sorbent were characterized by Fourier transform infrared (FT-IR) spectroscopy. The effect of various parameters including contact time, pH of oil solution, particle size, initial oil concentration and adsorbent dose on oil adsorption were investigated. The results showed that the adsorption kinetic was described by pseudo-second-order model. The change in the pH of oil solution from 2-10 had no effect on the oil adsorption. The decrease of particle size of DPTFs reduced oil sorption percent. The crude oil adsorption on DPTFs was well fitted by the Langmuir model. Maximum capacity of adsorption of crude oil by DPTFs was 2500 mg g-1. The results obtained revealed that crude oil adsorption onto the date palm wastes as the abundantly available low cost and readily biodegradable material is feasible and can successfully be used as an effective adsorbent to oil spill cleanup in water basins.